IMPROVING KEEPING QUALITY OF BUTTER BY UTILIZING MAILLARD REACTION PRODUCTS FROM HEATED WHEY - Mona Abd El-Gawad (Arab Universities Journal of Agricultural Sciences, 2007)
The antioxidaitve activity of Maillard reaction products MRPs) from heated whey added to butter was investigated. The antioxidant efficiency changed with different concentrations of MRPs used during storage period at 45ºC. Peroxide val-ue, thiobarbituric acid, acid value, carbonyl com-pounds and free fatty acids of butter were in-creased with storage. Their rate of increase de-creased with increasing the added amount of MRPs to butter.